Analisis Perbedaan Gender dalam Tingkat Kedisiplinan, Tingkat Kepercayaan Diri, dan Tingkat Kejujuran - Ni Ketut Anjani; Yadhurani Dewi Amritha (Journal on Education, 2024)
Discipline, self-confidence, and honesty are three important qualities that play a role in individual success in various areas of life. Often one of the factors that influences these three characteristics is gender. Gender, as a social and biological construct, plays an important role in shaping individual behavior, attitudes, and beliefs. The purpose of this study was to determine the effect of gender on the level of discipline, self-confidence, and accuracy in students. This study used quantitative research with data analysis techniques, namely logistic regression analysis with 105 samples, namely students in Denpasar City. The results of this study can be seen from the significance value, the first model can be stated as a model that can be used, namely gender can affect the level of discipline while the second and third models can be stated as gender cannot affect the level of self-confidence and honesty. Furthermore, the chance of a female student having a tendency towards discipline is 3.228 times greater than that of a male student.